2023
DOI: 10.1200/jco.22.01946
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Patients With Neuroblastoma After Assignment to Reduced Therapy Because of the 12- to 18-Month Change in Age Cutoff in Children's Oncology Group Risk Stratification

Abstract: PURPOSE In 2006, Children's Oncology Group (COG) reclassified subgroups of toddlers diagnosed with neuroblastoma from high-risk to intermediate-risk, when the age cutoff for high-risk assignment was raised from 365 days (12 months) to 547 days (18 months). The primary aim of this retrospective study was to determine if excellent outcome was maintained after assigned reduction of therapy. PATIENTS AND METHODS Children <3 years old at diagnosis, enrolled on a COG biology study from 1990 to 2018, were eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that children with NB in the high-risk group are most likely to develop bone marrow metastasis, and children with NB in the high-risk group are highly susceptible to recurrence because of minimal residual disease (MRD) in the bone marrow [12][13][14][15][16][17][18][19]. Bone marrow-associated neuroblastoma detection is crucial in diagnosing metastasis and recurrence in children with high-risk NB [2,3,8,13,[20][21][22][23][24][25]. However, there is a lack of consensus on the standard determination of NB bone marrow recurrence and metastasis globally [14][15][16]26], and the existing diagnostic techniques cannot solve the critical clinical challenges in children with high-risk NB.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that children with NB in the high-risk group are most likely to develop bone marrow metastasis, and children with NB in the high-risk group are highly susceptible to recurrence because of minimal residual disease (MRD) in the bone marrow [12][13][14][15][16][17][18][19]. Bone marrow-associated neuroblastoma detection is crucial in diagnosing metastasis and recurrence in children with high-risk NB [2,3,8,13,[20][21][22][23][24][25]. However, there is a lack of consensus on the standard determination of NB bone marrow recurrence and metastasis globally [14][15][16]26], and the existing diagnostic techniques cannot solve the critical clinical challenges in children with high-risk NB.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, several studies pointed out that certain high-risk neuroblastoma patients aged 12–18 months had favorable outcomes ( 18 ). Then, in 2006, with the aim to optimize treatment outcomes while minimizing exposure to treatment-related toxicities, the COG changed the age cut-off, from 12 to 18 months, which reclassified some patients from high to intermediate risk ( Figure 1 ) ( 19 ).…”
mentioning
confidence: 99%
“…While this re-classification saved children to be exposed to unnecessary treatments, their outcome should remain unaltered. Thus, Bender et al analyzed the outcome after the reclassification of the toddler’s groups diagnosed with neuroblastoma from the high-risk category to intermediate risk ( 19 ).…”
mentioning
confidence: 99%